Empirical Analysis of the Effects of Agricultural Cooperatives on Food Security among Smallholder Farmers in Benue State, Nigeria (Nigerian Journal of Cooperative Economics and Management, 2026)
Food security is major problem among households in Benue State of Nigeria. The main aim of the study was to analyze the effects of agricultural cooperatives on food security among smallholder farmers in Benue State, Nigeria. The specific objectives were: to examined the effect of cooperative membership duration on food security levels among smallholder farmers in Benue State; determine the effect of cooperatives credit access on food security of smallholder farmers in Benue State, and make recommendations based on findings. The study employed a survey research design, targeting 10,393 members of agricultural cooperatives. A sample of 385 cooperative members was selected using simple random sampling technique. A structured questionnaire yielded 354 valid responses, with validity confirmed by experts and reliability established with Cronbachs Alpha coefficient ranging from .970 to .981. Data were analyzed using regression analysis. Household Dietary Diversity Score was used to measure food security. Results revealed insignificant relationship between cooperative membership duration and food security levels(β=.461,p=.011), while access to cooperative credit showed a strong positive effect on food security of households(β= .598,p= .003). The study concludes that agricultural cooperatives are vital for enhancing food security among smallholder farmers and recommended that, there is a need to encouraged farmers to see cooperative membership as long term commitment, as the evidence shows that the most significant improvements in income and stability are achieved through sustained and active participation over years.
Keywords: Agricultural Cooperatives; Food Security; Smallholder-farmers